Clinical Features and Treatment Outcomes of Large Bladder Tumors Nearly Filling the Bladder - Akarken, Ilker; Tarhan, Huseyin; Karaoz, Fatih; Deliktas, Hasan; Dere, Yelda; Sahin, Hayrettin (Urology Journal, 2026)
Purpose: The prognosis and clinical management of bladder tumors nearly occupying the entire bladder cavity remain poorly defined due to limited available data. This study aimed to evaluate the clinical features and treatment outcomes of patients presenting with bladder tumors nearly filling the bladder at initial diagnosis. Materials and Methods: After obtaining ethical approval, a retrospective analysis was conducted on 51 patients diagnosed between 2017 and 2024 with primary bladder tumors nearly filling the bladder. All underwent transurethral resection of bladder tumor (TURBT). The clinical and pathological data were analyzed using descriptive statistics and multivariable logistic regression. Results: The mean age was 76.24 ± 11.7 years, with a median follow-up of 9.73 months (range: 3–84 months). Hematuria was the most frequent symptom (74.5%). Muscle-invasive disease was identified in 43.1% of cases at initial diagnosis, exceeding the 25% generally reported in newly diagnosed bladder cancer cohorts (p < .001). Complete resection was achieved in 68.6%, while 31.4% required repeat TURBT (re-TURBT). Among patients initially diagnosed with non-muscle-invasive tumors, 31.1% were found to have muscle invasion upon second resection. Treatments comprised intravesical immunotherapy (48.6%), radical cystectomy (25.7%), chemoradiation (14.3%), and systemic chemotherapy (11.4%). Conclusion: Bladder tumors nearly filling the bladder cavity are associated with high rates of muscle invasion and pose significant challenges in treatment and management. Larger, prospective multicenter studies are warranted to validate these findings and optimize management in this high-risk population.